Acute encephalopathy with biphasic seizures and late reduced diffusion associated with Streptococcus sanguinis sepsis - Hitoshi Awaguni; Jun Shinozuka; Shin-ichiro Tanaka; Sayaka Kadowaki; Shigeru Makino; Rikken Maruyama; Yosuke Shigematsu; Kenji Hamaoka; Shinsaku Imashuku (MDPI AG, 2018)
Acute encephalopathy with biphasic seizures and late reduced diffusion (AESD) develops in association with systemic as well as central nervous system (CNS) viral or bacterial infections. AESD is most often noted with influenza or human herpesvirus 6 infection in previously healthy infants. However, AESD has also been reported in an infant with developmental retardation and in a mentally and motor-disabled adolescent. Here, we report the case of a 4-year-old female with significant development delay due to spinal muscular atrophy, who developed AESD during Streptococcus sanguinis sepsis with no apparent CNS infection. Although the patient had extremely high serum procalcitonin (45.84 ng/mL, reference; <0.4) on admission indicating a poor prognosis, she was successfully managed for sepsis and AESD.